Evaluasi Kepuasan Mahasiswa terhadap Pelayanan Akademik dan Non-Akademik Di STIT Syamsul Ma’arif Bontang - Ihsan, Muh.; Asrianto, Asrianto (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study aims to evaluate the level of student satisfaction with academic and non-academic services at STIT Syamsul Ma’arif Bontang. The research employed a quantitative approach using a questionnaire distributed to 100 students from semesters 2, 4, 6, and 8. The findings indicate that, in general, students are fairly satisfied with academic services such as the learning process, academic advising, and the availability of lecturers. However, non-academic services such as campus facilities, administrative services, and student activities still require significant improvement. This study provides recommendations for enhancing service quality based on student needs.